MiR-21 modulates human airway smooth muscle cell proliferation and migration in asthma through regulation of PTEN expression. (26th November 2015) - Liu, Yun; Yang, Kunzheng; Shi, Hongyang; Xu, Jing; Zhang, Dexin; Wu, Yuanyuan; Zhou, Shuru; Sun, Xiuzhen
ABSTRACT: Background: Asthma is characterized by airway remodeling arising from an increase in airway smooth muscle (ASM) mass. This increase is regulated in part by ASM cell proliferation and migration. MicroRNA (miR)-21 also plays a role in asthma, but the molecular mechanisms underlying its effects are not completely understood. This study investigated the effects and mechanism of miR-21 on the human ASM (HASM) cell proliferation and migration. Materials and Methods: HASM cells were transduced with a miR-21 vector, and the expression of miR-21 was determined by quantitative real-time polymerase chain reaction (qRT-PCR). The effect of the miR-21 on HASM cell proliferation and migration was analyzed by CCK8 and transwell assay. The expression level of PTEN (phosphatase and tensin homolog deleted on chromosome 10) in HASM cells was assessed by qRT-PCR and Western blot analysis. Meanwhile, the activity of PTEN was measured by PTEN malachite green assay kit. Results: Lentivirus-mediated miR-21 overexpression markedly enhanced the proliferation and migration of HASM cells ( P < .05), and ablation of miR-21 by anti-miR-21 inhibitor markedly reduced cell proliferation and migration. We demonstrated that miR-21 overexpression significantly reduced the expression of PTEN ( P < .05), while PTEN knock-down markedly increased HASM cell proliferation and migration. Furthermore, we found that overexpression of PTEN led to a decrease of HASM cell proliferation and migration. MiR-21 mediated HASM cell proliferation and migration through activation of the phosphoinositide 3-kinase pathway. Conclusions: This study provides the first in vitro evidence that overexpression of miR-21 in HASM cells can trigger cell proliferation and migration, and the effects of miR-21 depend on the level of PTEN.